Redescription of Neocarus platensis Silvestri, 1905 (Acari: Opilioacaridae) and a new species from the syntype series - De Araújo, Marcel Santos; Di Palma, Antonella; Feres, Reinaldo José Fazzio; Penteado-Dias, Angelica Maria (Zootaxa, 2023)
Neocarus platensis is redescribed from part of the syntype series collected in Argentina and lectotype specimens are designated. The remaining syntype material from Uruguay represents a new species, herein named Neocarus paraplatensis sp. nov. Taxonomic problems within the Opilioacaridae are discussed in light of a comparative morphological discussion including setae quantity variation.